PEMANFAATAN APALIKASI MOBILE EDUKATIF SEBAGAI MEDIA PEMBELAJARAN KREATIF BAGI ANAK USIA DINI DI DESA DALU SEPULUH B - Sembiring, Muhammad Ardiansyah; Sibuea, Mustika Fitri Larasati; Selvi, Diana (Jurnal Pemberdayaan Sosial dan Teknologi Masyarakat, 2025)
Abstract: Early childhood learning requires creative and engaging media to stimulate cognitive, motor, and creativity development. At TK Mutiara Amaliah, Desa Dalu Sepuluh B, Kecamatan Tanjung Morawa, the use of educational mobile applications has not been optimal because teachers are not yet accustomed to using digital media as a learning aid, while students have not received interactive, technology-based learning experiences. This community service activity aims to improve teachers’ abilities in selecting and utilizing educational mobile applications as creative learning media, as well as to provide direct learning experiences to kindergarten students using age-appropriate and safe applications. The program will be implemented on June 19, 2025, including teacher training on the use of educational applications, practical integration of the applications into learning activities, and interactive learning sessions with students. The target outputs of this activity include: (1) improved teacher competence in using educational applications, (2) increased creativity and learning motivation of TK Mutiara Amaliah students, (3) the development of a guidebook for using educational applications, and (4) publication of the community service activity report. Through this program, learning is expected to become more innovative and aligned with digital technology developments. The community service activity was successfully implemented and received positive responses from both teachers and students at TK Mutiara Amaliah. Teachers were able to understand how to operate Virtual Reality–based mobile applications and successfully integrate them into learning activities. Students showed high enthusiasm and improved creativity during the interactive VR learning sessions. Overall, the activity has made a significant impact on enhancing the quality of learning and the use of technology within the school environment.            Keywords: Educational Applications; Creative Learning; Early Childhood; Kindergarten Teachers; Educational Technology Abstrak: Pembelajaran anak usia dini membutuhkan media yang kreatif dan menarik untuk menstimulasi perkembangan kognitif, motorik, dan kreativitas. Di TK Mutiara Amaliah, Desa Dalu Sepuluh B, Kecamatan Tanjung Morawa, pemanfaatan aplikasi mobile edukatif masih belum optimal karena guru belum terbiasa menggunakan media digital sebagai pendukung kegiatan belajar, sementara siswa belum mendapat pengalaman belajar interaktif berbasis teknologi. Kegiatan pengabdian masyarakat ini bertujuan meningkatkan kemampuan guru dalam memilih dan memanfaatkan aplikasi mobile edukatif sebagai media pembelajaran kreatif, serta memberikan pengalaman belajar langsung kepada siswa TK melalui aplikasi yang sesuai usia dan aman digunakan. Program akan dilaksanakan pada 19 Juni 2025, meliputi pelatihan guru mengenai penggunaan aplikasi edukatif, praktik integrasi aplikasi ke dalam kegiatan belajar, dan sesi pembelajaran interaktif bersama siswa. Target luaran kegiatan ini mencakup: (1) peningkatan kompetensi guru dalam menggunakan aplikasi edukatif, (2) meningkatnya kreativitas dan minat belajar siswa TK Mutiara Amaliah, (3) tersusunnya modul panduan penggunaan aplikasi edukatif, dan (4) publikasi laporan kegiatan pengabdian. Dengan kegiatan ini, diharapkan pembelajaran menjadi lebih inovatif dan sesuai perkembangan teknologi digital. Kegiatan pengabdian masyarakat berjalan dengan baik dan mendapat respons positif dari guru serta siswa TK Mutiara Amaliah. Guru mampu memahami cara pengoperasian aplikasi mobile berbasis Virtual Reality dan berhasil mengintegrasikannya ke dalam kegiatan pembelajaran. Siswa menunjukkan antusiasme tinggi serta peningkatan kreativitas saat mengikuti sesi pembelajaran interaktif menggunakan VR. Secara keseluruhan, kegiatan ini memberikan dampak nyata terhadap peningkatan kualitas pembelajaran dan pemanfaatan teknologi di lingkungan sekolah. Kata kunci: Aplikasi Edukatif; Pembelajaran Kreatif; Anak Usia Dini; Guru TK; Teknologi Pendidikan